A Review of Healthcare Challenges in the UK and the US: Medical Errors, Aging, Private Healthcare and Governance - John S. Bolwell (Health Sciences Review)
Deaths and serious injuries caused by medical errors continue to beset the healthcare systems of all developed countries. Most are due to failures in the processes of care exacerbated by poor communication between healthcare providers and with patients, particularly the elderly with varying degrees of cognitive impairment. The global phenomenon of aging populations due to declining birthrates and increased life expectancy may have detrimental consequences for societies and is briefly considered. The most common medical errors are failure to diagnose, misdiagnoses, failure to treat, surgical and anesthetic errors, negligent postoperative care, medication errors, failure to order, or act on, laboratory tests, and birth injuries (mother and baby). Estimated numbers of deaths vary widely, for example 22,000 to 40,000 in the UK and 98,000 to 251,000 in the US which attests to the complexity of accurate quantification. Regardless of the true magnitude there is no doubt that several deaths due to preventable medical errors occur in each hospital every year and there are 1,148 public and private hospitals in the UK and 6,120 in the US. The history and efficacy of preventative measures such as continuing professional development, continuity of care, multi-disciplinary-team management and quality assurance programs are summarized. The UK and the US have worse healthcare outcomes and shorter average life expectancies than comparable developed countries and these issues are discussed. Reforms which might contribute to the delivery of safe, universal and sustainable healthcare in the UK and the US are reviewed.